Effective Learning Strategies: Minimum Completeness Criteria and Remedial Program as an Effort to Improve Physics Learning on Dynamic Fluid Material - Rahmat Perdana; Sri Wina Oktavia; Feliza Paramitha Sinaga (Journal Evaluation in Education (JEE), 2024)
Purpose of the study: This study aims to analyze the use of Minimum Competency Criteria and remedial programs in learning Physics in schools. Methodology: This mixed-methods research involved all students of Surya Ibu Jambi Private Senior High School, with a sample of 50 students selected through purposive sampling. Data were collected using questions, questionnaires, and interviews, and analyzed using descriptive statistical tests. Main Findings: The results indicated that the implementation of Minimum Competency Criteria and remedial programs at Surya Ibu Jambi Private Senior High School falls within the good category. Novelty/Originality of this study: This study provides insights into the effectiveness of Minimum Competency Criteria and remedial programs in enhancing students’ understanding and performance in Physics. Positive results could underscore the importance of these strategies in improving learning outcomes in schools.